DEVELOPMENT OF STUDENTS’ CREATIVITY SKILLS BASED ON INTERACTIVE TEACHING METHODS AND TECHNOLOGIES - Shermamatova , Zaynab Azimjonovna; Egamberdiyev , Otanazar Erkin oʻgʻli; Ergasheva , Maftuna Abdimital qizi (Educational Research in Universal Sciences, 2023)
In the article, there is a scientific-practical discussion of the harmony of educational and physiological processes related to the reading activity of students in the primary school period, and the issues of proper development of the child’s perception in this process. Information provided.